THE DISSEMINATION OF TRADITIONAL CHINESE CULTURE IN THAI SCHOOLS FROM CHINESE TEACHERS’ PERSPECTIVE - Xu, Weijie (Chinese Journal of Social Science and Management, 2021)
As the main communicator of Chinese traditional culture in Thailand, the Chinese teacher who teach Chinese in Thailand, have made a great contributions to the Chinese teaching and the cultural communication in Thailand. This article focus on investigate the propagation of traditional Chinese culture by Chinese teachers. And response to the problems and obstacles encountered in the communication process, some specific solutions were summarized to provide references for the communication of traditional Chinese culture and Chinese teaching in Thailand. This article selected 45 Chinese teachers from 20 universities and schools, and collect the data through interviews. This article analyzes the problems and causes of the spread of Chinese traditional culture in Thailand, and the promotion effect of the spread and application of Chinese traditional culture in Chinese teaching in Thailand. Based on the analysis results, it is concluded that Chinese traditional culture is spreading well in Thailand, and the schools in Thailand gradually increase the proportion of cultural teaching, but there are still some deficiencies in the teaching materials. As disseminators of Chinese traditional culture, teachers should not only improve their own cultural literacy, but also adopt more appropriate teaching methods for different students to better spread culture, and promote the overall improvement of students’ Chinese proficiency through cultural teaching.